UPAYA PENEGAKAN HUKUM ATAS PEREDARAN FILM TANPA IZIN SEBAGAI BENTUK PELANGGARAN HAK CIPTA MELALUI APLIKASI TELEGRAM - Kadek Rio Gunawan; Rohaini; Bayu Sujadmiko (Rechtsregel : Jurnal Ilmu Hukum, 2025)
The development of digital technology has facilitated the access and distribution of copyrighted works, but on the other hand it also increases the potential for copyright infringement, especially through communication platforms such as Telegram. This research aims to analyze the form of law enforcement against the distribution of unlicensed films through the Telegram application as copyright infringement in Indonesia. The formulation of the problem raised includes how the law enforcement mechanism against copyright infringement in the digital space and the challenges faced in the context of jurisdiction and legal proof. The research method used is normative juridical with a statutory approach and case studies, supported by secondary data in the form of laws and regulations, court decisions, and related literature. The results show that although Law Number 28 of 2014 on Copyright and Law Number 11 of 2008 on Electronic Information and Transactions (ITE) have adequately regulated copyright protection, the implementation of law enforcement against infringement through Telegram still experiences obstacles, including limited access to data on perpetrators, not optimal international cooperation, and weak public digital literacy. The conclusion of this study emphasizes the need for increased synergy between law enforcement officials, platform providers, and copyright owners in forming an effective mechanism to tackle digital copyright infringement.